Higher education and sustainable development: Exploring possibilities for organisational change. Issue 2 (7th February 2014) - Godemann, Jasmin; Bebbington, Jan; Herzig, Christian; Moon, Jeremy
Abstract : Purpose: – This paper seeks to create the context within which research into how higher education institutions (HEIs) might engage with the goal of sustainable development. In particular, the paper outlines the context in which papers in a special section on this topic might be understood as well as developing propositions for how a research focus might emerge in this area. The paper, therefore, seeks to contribute to discussions about whether, under which circumstances and how social accountability and engagement processes focusing on sustainable development might trigger, frame and/or promote change processes in HEIs. The papers that compose this special section are also introduced and future research avenues offered. Design/methodology/approach: – Literature review Findings: – Despite a dearth of literature in the area of HEI responsiveness to sustainable development (and leaving side education/learning and research for sustainable development), numerous points of intersection exist. Foremost among these is the role of HEIs as shapers of the values of society (and a place for debates about these values). In addition, HEIs are substantive organisations with sustainable development impacts. The paper suggests, however, that understanding HEIs and self-consciously seeking change in their activities has to seriously engage with the characterisation of these organisations as loosely coupled systems. Originality/value: – The paper discusses the distinctive characteristics of HEIs and considers the higher education context as a challenging case to explore the capacity of social accountability and stakeholder engagement to foster change towards the goal of sustainable development.